Calamus nambariensis Becc. (Arecaceae Schultz-sch.) - a new species for the flora of Vietnam - Anh, Tran Phuong; Khoi, Nguyen Khac (Academia Journal of Biology, 2014)
The genus Calamus L. (Arecaceae Schultz.-Sch.) has 370 species in the world, with wide distribution from the tropics of Africa, India, China to Australia. There are 21 species in Vietnam. During the study, we have found one species as new record (Calamus nambariensis Becc.) for the flora of Vietnam. This species can be recognized by: climbing, clustering, cirrus; knee present; sheath has mixture of long and short spines; leaflets grouped, regular at the base, boat-shape (40-55 ´ 2.5-7 cm); inflorescence no flagellum. This species closes to Calamus platyacanthus Warrb. ex Becc. but differs by: leaflet regular at the base; sheath spine shorter (shorter 4 cm); fruit oblong. This species is collected in the Chamchu natural reserve, Tuyenquang province.